Presidents between national unity and ethnic divisions: public trust across the Baltic states. Issue 2 (3rd April 2023) - Duvold, Kjetil; Sedelius, Thomas
ABSTRACT: The Baltic presidents have in common that they are supposed to embody the 'nation' and provide an image of their countries abroad. But can the president embody the people if 'the people' itself is divided? In this article, we will focus on public trust in the presidency between the majority and minority population in the Baltic states. Drawing on public opinion surveys, the aim is to examine the determinants of public trust in the presidential institution and support for the performance and principles of the political system as well identification with the political community itself. Among our findings, we conclude that ethnic or linguistic identity explains trust to a considerable degree, which suggests that trust is not only an expression of specific political support, but also part of a more deep-seated, diffuse support.